(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The research was performed by planting three lines of barley (Hordeum vulgare L.) individually or in mixtures with peas (Pisum sativum L.). This study was carried out in Randomized Complete Block Design (RCBD) and four replicates at Dibba Agricultural Research Station between 2016 and 2017. The response of barley lines to these applied farming systems in stem elongation, booting and maturation stages has been studied by measuring the growth and development plant, the competition indices between the studied lines, the dry matter production, the yield and the total relative yield of the lines and the pea contribution (%) in mixtures. The results indicated that the booting stage is the best to produce the highest yield whether in mixed or single farming systems. Barley lines 2 and 3 were superior (P<0.05)to line 1 in the all characteristics and traits studied and at different stages of growth. Barley mixtures 1 and 2 showed a higher percentage of legumes (%) basis on dry weight compared to these of the line 3 or individual agriculture for each line. We conclude that the lines planted in mixtures have a great ability to benefit from the available environmental conditions, which have had a positive effect on plant growth and productivity compared with the individual agriculture. نُفذ البحث في محطة دبا للبحوث الزراعية بين عامي 2016-2017 بزراعة ثلاث سلالات مبشرة من الشعير (Hordeum vulgare L.) في قطع تجريبية بشكل منفرد أو ضمن خلائط مع البازلاء العلفية (Pisum sativum L.)، تم تصميم التجربة بنظام القطاعات العشوائية الكاملة (RCBD) وبأربع مكررات للمعاملة الواحدة. درس العمل استجابة سلالات الشعير في مرحلة تطاول الساق، الحبل والنضج لهذه النظم الزراعية المطبقة من حيث النمو والتطور ومؤشرات التنافس بين السلالات المدروسة، إنتاجية المادة الجافة، الغلة الحبية وإجمالي الغلة النسبية للسلالات ونسبة (%) مساهمة البازلاء في معاملات الخلائط. أشارت النتائج لأن طور الحبل هو الموعد الأفضل للحصول على أعلى إنتاجية للسلالات المدروسة سواءً في نظام الزراعة المختلطة أم المنفردة. تفوقت سلالات الشعير2 و3 على السلالة1 معنوياً (P<0.05) في مجمل الخصائص والصفات المدروسة وعند مختلف مراحل النمو. أظهرت خلائط سلالتي الشعير1 و2 نسبة أعلى للبقوليات (%) على أساس الوزن الجاف وذلك بالمقارنة مع خلائط السلالة 3 أو الزراعة المنفردة لكل سلالة. نخلص مما سبق، بأن السلالات المزروعة في خلائط تمتعت بمقدرة كبيرة على الاستفادة من الظروف البيئية المتاحة والذي انعكس إيجاباً على نمو النبات وإنتاجيته مقارنة مع الزراعة المنفردة.